Square Roots

When we encounter an exercise in which there is a root applied to another root, we will multiply the order of the first root by the order of the second and the order obtained (the product of both) will be raised as a root in our number (as generally power of a power)
Let's put it this way:  

root of root unknowns

Suggested Topics to Practice in Advance

  1. Square root of a product
  2. Square root of a quotient

Practice Root of a Root

Examples with solutions for Root of a Root

Exercise #1

Solve the following exercise:

4= \sqrt{\sqrt{4}}=

Video Solution

Step-by-Step Solution

To solve the expression 4\sqrt{\sqrt{4}}, we'll proceed with the following steps:

  • Step 1: Evaluate the inner square root.
    The expression 4\sqrt{4} simplifies to 2, because 2 squared is 4.
  • Step 2: Now evaluate the square root of 2.
    Since the result from step 1 is 2, we need to find 2\sqrt{2}. This is the prime representation of the result because 2 cannot be further simplified.

Therefore, the answer to the problem 4\sqrt{\sqrt{4}} is 2\sqrt{2}.

Answer

2 \sqrt{2}

Exercise #2

Solve the following exercise:

12= \sqrt{\sqrt{12}}=

Video Solution

Step-by-Step Solution

In order to solve the following expression 12 \sqrt{\sqrt{12}} , it needs to be simplified using the properties of exponents and roots. Specifically, we apply the rule that states that the square root of a square root can be expressed as a fourth root.

Let's break down this solution step by step:

  • First, represent the inner 12 \sqrt{12} as a power: 121/2 12^{1/2} .

  • Next, take the square root of this result, which involves raising 121/2 12^{1/2} to the power of 1/2 1/2 again:
    (121/2)1/2=12(1/2)(1/2)=121/4\left(12^{1/2}\right)^{1/2} = 12^{(1/2) \cdot (1/2)} = 12^{1/4}.

  • According to the rules of exponents, raising an exponent to another power results in multiplying the exponents.

  • This gives us 121/4 12^{1/4} , which we can write as the fourth root of 12: 124 \sqrt[4]{12} .

In conclusion the simplification of 12 \sqrt{\sqrt{12}} is 124 \sqrt[4]{12} .

Answer

124 \sqrt[4]{12}

Exercise #3

Solve the following exercise:

26= \sqrt[6]{\sqrt{2}}=

Video Solution

Step-by-Step Solution

In order to solve this problem, we must simplify the following expression 26 \sqrt[6]{\sqrt{2}} using the rule for roots of roots. This rule states that a root of a root can be written as a single root by multiplying the indices of the radicals.

  • Step 1: Identify the given expression 26 \sqrt[6]{\sqrt{2}} .

  • Step 2: Recognize that the inner root, 2\sqrt{2}, can be expressed as 22\sqrt[2]{2}.

  • Step 3: Visualize 26 \sqrt[6]{\sqrt{2}} as 226 \sqrt[6]{\sqrt[2]{2}} .

  • Step 4: Apply the rule amn=an×m\sqrt[n]{\sqrt[m]{a}} = \sqrt[n \times m]{a}.

  • Step 5: Multiply the indices: 6×2=126 \times 2 = 12.

  • Step 6: Replace the compound root with the single root: 212\sqrt[12]{2}.

Thus, the expression 26 \sqrt[6]{\sqrt{2}} simplifies to 212 \sqrt[12]{2} .

Therefore, the solution to the problem is 212 \sqrt[12]{2} .

Answer

212 \sqrt[12]{2}

Exercise #4

Solve the following exercise:

8= \sqrt[]{\sqrt{8}}=

Video Solution

Step-by-Step Solution

In order to solve the given problem, we'll follow these steps:

  • Step 1: Convert the inner square root to an exponent: 8=81/2\sqrt{8} = 8^{1/2}.

  • Step 2: Apply the root of a root property: 8=(8)1/2=(81/2)1/2\sqrt{\sqrt{8}} = (\sqrt{8})^{1/2} = (8^{1/2})^{1/2}.

  • Step 3: Simplify the expression using exponent rules: (81/2)1/2=8(1/2)(1/2)=81/4(8^{1/2})^{1/2} = 8^{(1/2) \cdot (1/2)} = 8^{1/4}.

The nested root expression simplifies to 81/48^{1/4}.

Therefore, the simplified expression of 8\sqrt{\sqrt{8}} is 814 8^{\frac{1}{4}} .

After comparing this result with the multiple choice answers, choice 2 is correct.

Answer

814 8^{\frac{1}{4}}

Exercise #5

Solve the following exercise:

26= \sqrt[6]{\sqrt{2}}=

Video Solution

Step-by-Step Solution

Express the definition of root as a power:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

Remember that in a square root (also called "root to the power of 2") we don't write the root's power as shown below:

n=2 n=2

Meaning:

a=a2=a12 \sqrt{a}=\sqrt[2]{a}=a^{\frac{1}{2}}

Now convert the roots in the problem using the root definition provided above. :

26=2126=(212)16 \sqrt[6]{\sqrt{2}}=\sqrt[6]{2^{\frac{1}{2}}}=\big(2^{\frac{1}{2}}\big)^{\frac{1}{6}}

In the first stage we applied the root definition as a power mentioned earlier to the inner expression (meaning inside the larger-outer root) and then we used parentheses and applied the same definition to the outer root.

Let's recall the power law for power of a power:

(am)n=amn (a^m)^n=a^{m\cdot n}

Apply this law to the expression that we obtained in the last stage:

(212)16=21216=21126=2112 \big(2^{\frac{1}{2}}\big)^{\frac{1}{6}}=2^{\frac{1}{2}\cdot\frac{1}{6}}=2^{\frac{1\cdot1}{2\cdot6}}=2^{\frac{1}{12}}

In the first stage we applied the power law mentioned above and then proceeded first to simplify the resulting expression and then to perform the multiplication of fractions in the power exponent.

Let's summarize the various steps of the solution thus far:

26=(212)16=2112 \sqrt[6]{\sqrt{2}}=\big(2^{\frac{1}{2}}\big)^{\frac{1}{6}} =2^{\frac{1}{12}}

In the next stage we'll apply once again the root definition as a power, (that was mentioned at the beginning of the solution) however this time in the opposite direction:

a1n=an a^{\frac{1}{n}} = \sqrt[n]{a}

Let's apply this law in order to present the expression we obtained in the last stage in root form:

2112=212 2^{\frac{1}{12}} =\sqrt[12]{2}

We obtain the following result: :

26=2112=212 \sqrt[6]{\sqrt{2}}=2^{\frac{1}{12}} =\sqrt[12]{2}

Therefore the correct answer is answer A.

Answer

212 \sqrt[12]{2}

Exercise #6

Solve the following exercise:

11010= \sqrt[10]{\sqrt[10]{1}}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll observe the following process:

  • Step 1: Recognize the expression 11010 \sqrt[10]{\sqrt[10]{1}} involves nested roots.
  • Step 2: Apply the formula for nested roots: xmn=xnm \sqrt[n]{\sqrt[m]{x}} = \sqrt[n \cdot m]{x} .
  • Step 3: Set n=10 n = 10 and m=10 m = 10 , resulting in 110×10=1100 \sqrt[10 \times 10]{1} = \sqrt[100]{1} .
  • Step 4: Simplify 1100 \sqrt[100]{1} . Any root of 1 is 1, as 1k=1 1^k = 1 for any positive rational number k k .

Thus, the evaluation of the original expression 11010 \sqrt[10]{\sqrt[10]{1}} equals 1.

Comparing this result to the provided choices:

  • Choice 1 is 1 1 .
  • Choice 2 is 1100 \sqrt[100]{1} , which is also 1.
  • Choice 3 is 1=1 \sqrt{1} = 1 .
  • Choice 4 states all answers are correct.

Therefore, choice 4 is correct: All answers are equivalent to the solution, being 1.

Thus, the correct selection is: All answers are correct.

Answer

All answers are correct.

Exercise #7

Solve the following exercise:

535= \sqrt[5]{\sqrt[3]{5}}=

Video Solution

Step-by-Step Solution

To solve the problem of finding 535 \sqrt[5]{\sqrt[3]{5}} , we'll use the formula for a root of a root, which combines the exponents:

  • Step 1: Express each root as an exponent.
    We start with the innermost root: 53=51/3 \sqrt[3]{5} = 5^{1/3} .
  • Step 2: Apply the outer root.
    The square root to the fifth power is expressed as: 51/35=(51/3)1/5 \sqrt[5]{5^{1/3}} = (5^{1/3})^{1/5} .
  • Step 3: Combine the exponents.
    Using the exponent rule (am)n=am×n(a^m)^n = a^{m \times n}, we get:
    (51/3)1/5=5(1/3)×(1/5)=51/15(5^{1/3})^{1/5} = 5^{(1/3) \times (1/5)} = 5^{1/15}.
  • Step 4: Convert the exponent back to root form.
    This can be written as 515 \sqrt[15]{5} .

Therefore, the simplified expression of 535 \sqrt[5]{\sqrt[3]{5}} is 515 \sqrt[15]{5} .

Answer

515 \sqrt[15]{5}

Exercise #8

Solve the following exercise:

2= \sqrt{\sqrt{2}}=

Video Solution

Step-by-Step Solution

To solve 2\sqrt{\sqrt{2}}, we will use the property of roots.

  • Step 1: Recognize that 2\sqrt{\sqrt{2}} involves two square roots.
  • Step 2: Each square root can be expressed using exponents: 2=21/2\sqrt{2} = 2^{1/2}.
  • Step 3: Therefore, 2=(21/2)1/2\sqrt{\sqrt{2}} = (2^{1/2})^{1/2}.
  • Step 4: Apply the formula for the root of a root: (xa)b=xab(x^{a})^{b} = x^{ab}.
  • Step 5: For (21/2)1/2(2^{1/2})^{1/2}, this means we compute the product of the exponents: (1/2)×(1/2)=1/4(1/2) \times (1/2) = 1/4.
  • Step 6: The expression simplifies to 21/42^{1/4}, which is written as 24\sqrt[4]{2}.

Therefore, 2=24\sqrt{\sqrt{2}} = \sqrt[4]{2}.

This corresponds to choice 2: 24 \sqrt[4]{2} .

The solution to the problem is 24 \sqrt[4]{2} .

Answer

24 \sqrt[4]{2}

Exercise #9

Solve the following exercise:

1443= \sqrt[3]{\sqrt{144}}=

Video Solution

Step-by-Step Solution

To solve this problem, let's follow these steps:

  • Express the square root as a fractional exponent.
  • Express the cube root as another fractional exponent.
  • Multiply the exponents together using the rule (am)n=am×n(a^m)^n = a^{m \times n}.
  • Recapture the result as a root expression.

Let's apply these steps:
Step 1: The square root of 144 can be expressed as 1441/2144^{1/2}.
Step 2: We need the cube root of this expression, so we have (1441/2)1/3(144^{1/2})^{1/3}.
Step 3: Using the property of exponents (am)n=am×n(a^m)^n = a^{m \times n}, we multiply the exponents: (1441/2)1/3=144(1/2)×(1/3)=1441/6(144^{1/2})^{1/3} = 144^{(1/2) \times (1/3)} = 144^{1/6}.
Step 4: Re-express this as a root: Since 1441/6144^{1/6} is equivalent to the sixth root, we have 1446\sqrt[6]{144}.

Therefore, the solution to the problem is 1446\sqrt[6]{144}, which corresponds to choice 3.

Answer

1446 \sqrt[6]{144}

Exercise #10

Complete the following exercise:

5x4= \sqrt[]{\sqrt{5x^4}}=

Video Solution

Step-by-Step Solution

To solve the expression 5x4\sqrt[]{\sqrt{5x^4}}, let's go step-by-step:

  • Step 1: Simplify the inner expression 5x4\sqrt{5x^4}. Using the rule for square roots, we can rewrite 5x4\sqrt{5x^4} as (5x4)1/2(5x^4)^{1/2}. This expression can be further simplified to 51/2(x4)1/2=5x25^{1/2} \cdot (x^4)^{1/2} = \sqrt{5} \cdot x^2.
  • Step 2: Take the square root of the simplified expression. This means we apply another square root to 5x2\sqrt{5} \cdot x^2, resulting in (5x2)1/2=(5)1/2(x2)1/2(\sqrt{5} \cdot x^2)^{1/2} = (\sqrt{5})^{1/2} \cdot (x^2)^{1/2}.
  • Step 3: Simplify each component: 54x\sqrt[4]{5} \cdot x. We find that (5)1/2(\sqrt{5})^{1/2} simplifies to 54\sqrt[4]{5} and (x2)1/2(x^2)^{1/2} to xx.

Therefore, the simplified expression is 54x \sqrt[4]{5} \cdot x .

Answer

54x \sqrt[4]{5}\cdot x

Exercise #11

Complete the following exercise:

x88= \sqrt[8]{\sqrt{x^8}}=

Video Solution

Step-by-Step Solution

To solve the problem x88 \sqrt[8]{\sqrt{x^8}} , we'll simplify the expression using exponent rules:

  • Step 1: Express the inner square root using exponents. We know x8=(x8)1/2=x81/2=x4 \sqrt{x^8} = (x^8)^{1/2} = x^{8 \cdot 1/2} = x^4 .
  • Step 2: Express the entire expression with the 8th root as an exponent. We have x48=(x4)1/8 \sqrt[8]{x^4} = (x^4)^{1/8} .
  • Step 3: Simplify the expression, using (xa)b=xab (x^a)^{b} = x^{a \cdot b} . Therefore, (x4)1/8=x41/8=x1/2 (x^4)^{1/8} = x^{4 \cdot 1/8} = x^{1/2} .
  • Step 4: Recognize x1/2 x^{1/2} is another way to write x \sqrt{x} .

Thus, the expression simplifies to x \sqrt{x} .

Answer

x \sqrt{x}

Exercise #12

Complete the following exercise:

64x12=3 \sqrt[3]{\sqrt{64\cdot x^{12}}=}

Video Solution

Step-by-Step Solution

To solve the problem 64x123 \sqrt[3]{\sqrt{64 \cdot x^{12}}} , follow these detailed steps:

  • Step 1: Simplify the inner expression.
    The expression inside the radical is 64x12 64 \cdot x^{12} .
  • Step 2: Simplify the inner square root.

    First, we need to find 64x12 \sqrt{64 \cdot x^{12}} .

    The square root of a product can be expressed as the product of the square roots: 64x12 \sqrt{64} \cdot \sqrt{x^{12}} .

    Simplifying further, we find:

    • 64=8 \sqrt{64} = 8 , since 82=64 8^2 = 64 .
    • x12=x6 \sqrt{x^{12}} = x^{6} , because (x6)2=x12 (x^{6})^2 = x^{12} .

    Thus, the inner square root becomes 8x6 8x^6 .

  • Step 3: Simplify using the cube root.

    Next, apply the cube root to the result of the inner square root: 8x63 \sqrt[3]{8x^6} .

    The cube root of a product can also be expressed as the product of the cube roots:

    • 83=2 \sqrt[3]{8} = 2 , since 23=8 2^3 = 8 .
    • x63=x6/3=x2 \sqrt[3]{x^6} = x^{6/3} = x^{2} , because (x2)3=x6 (x^2)^3 = x^6 .

    Thus, the expression simplifies to 2x2 2x^2 .

Therefore, the solution to this problem is 2x2 2x^2 , which corresponds to choice 2 in the provided options.

Answer

2x2 2x^2

Exercise #13

Complete the following exercise:

81x4= \sqrt{\sqrt{81\cdot x^4}}=

Video Solution

Step-by-Step Solution

To solve the problem 81x4 \sqrt{\sqrt{81 \cdot x^4}} , we need to simplify this expression using properties of exponents and square roots.

  • Step 1: Simplify the inner square root
    The expression inside the first square root is 81x4 81 \cdot x^4 . We can rewrite this using exponents:
    81=92 81 = 9^2 and x4=(x2)2 x^4 = (x^2)^2 . Thus, 81x4=(9x2)2 81 \cdot x^4 = (9x^2)^2 .
  • Step 2: Apply the inner square root
    Taking the square root of (9x2)2 (9x^2)^2 gives us:
    (9x2)2=9x2 \sqrt{(9x^2)^2} = 9x^2 , because a2=a \sqrt{a^2} = a where a a is a non-negative real number.
  • Step 3: Simplify the outer square root
    Now, we take the square root of the result from the inner root:
    9x2=9x2=3x=3x \sqrt{9x^2} = \sqrt{9} \cdot \sqrt{x^2} = 3 \cdot x = 3x , since x2=x \sqrt{x^2} = x given x x is non-negative.

Therefore, the solution to the problem is 3x 3x .

Answer

3x 3x

Exercise #14

Complete the following exercise:

16x2= \sqrt{\sqrt{16\cdot x^2}}=

Video Solution

Step-by-Step Solution

To solve the expression 16x2 \sqrt{\sqrt{16 \cdot x^2}} , follow these steps:

  • Step 1: Simplify the innermost root 16x2 \sqrt{16 \cdot x^2} .
    Here, apply ab=ab \sqrt{a \cdot b} = \sqrt{a} \cdot \sqrt{b} . Thus, 16x2=16x2 \sqrt{16 \cdot x^2} = \sqrt{16} \cdot \sqrt{x^2} .
  • Step 2: Calculate each component:
    - 16=4 \sqrt{16} = 4 because 161/2=4 16^{1/2} = 4 .
    - x2=x \sqrt{x^2} = x assuming x x is non-negative.
  • Step 3: Combine results from Step 2: 16x2=4x=4x \sqrt{16} \cdot \sqrt{x^2} = 4 \cdot x = 4x .
  • Step 4: Simplify the outer square root: 4x \sqrt{4x} .
    Applying 4x=4x \sqrt{4x} = \sqrt{4} \cdot \sqrt{x} , we have 4=2 \sqrt{4} = 2 .
    Thus, 4x=2x=2x \sqrt{4x} = 2 \cdot \sqrt{x} = 2\sqrt{x} .

Therefore, the simplified form of 16x2 \sqrt{\sqrt{16 \cdot x^2}} is 2x 2\sqrt{x} . This corresponds to choice 1.

Answer

2x 2\sqrt{x}

Exercise #15

Complete the following exercise:

3x2= \sqrt{\sqrt{3x^2}}=

Video Solution

Step-by-Step Solution

To solve 3x2\sqrt{\sqrt{3x^2}}, follow these steps:

  • Step 1: Express the problem using exponentiation. The expression 3x2\sqrt{3x^2} can be written as (3x2)12(3x^2)^{\frac{1}{2}}.
  • Step 2: Take the square root of the first expression. This can be expressed as ((3x2)12)12((3x^2)^{\frac{1}{2}})^{\frac{1}{2}}.
  • Step 3: Use the property (am)n=amn(a^m)^n = a^{m \cdot n}. Thus, ((3x2)12)12=(3x2)14((3x^2)^{\frac{1}{2}})^{\frac{1}{2}} = (3x^2)^{\frac{1}{4}}.
  • Step 4: Simplify further using exponent rules: (3x2)14(3x^2)^{\frac{1}{4}} becomes (314(x2)14)(3^{\frac{1}{4}} \cdot (x^2)^{\frac{1}{4}}), which simplifies to 34x12\sqrt[4]{3} \cdot x^{\frac{1}{2}}.
  • Step 5: Recognize this as 34x\sqrt[4]{3} \cdot \sqrt{x}, since x12x^{\frac{1}{2}} is x\sqrt{x}.

Therefore, the simplified form of the given expression is 34x \sqrt[4]{3} \cdot \sqrt{x} .

Answer

34x \sqrt[4]{3}\cdot\sqrt{x}